Conservação de água em escolas com ênfase em aproveitamento de água de chuva : estudo de caso nas escolas da rede municipal de Erechim-RS - Faresin, Andréia Eugenia (2008)
Water protects a rich ecosystem from which man extracts foods, moves hydroelectric power plants, supplies cities. Water is a finite benefit. Besides rationalization of water use, we must take into account the possibility of the utilization of water alternative sources, like rain water, that is a water source easily available and usually directed to nets and drainage systems, without use. But we must have an appropriate system of rain water utilization to each case, not compromising its credibility and security of its users. Thus, the objective of this work is arouse to preservation and the importance of environmental consciousnessraising through rationalization of water use and utilization of water alternative sources to non drinkable use at Municipal Net Schools in Erechim, RS. To it, the methodology based itself on research at Schools, with survey of dada necessary to a preliminary diagnosis of water consumption and application of a methodology of implantation of Utilization Systems of pluvial water. With the results obtained, we have a project of utilization of pluvial water to Paiol Grande School, conceived within the applied methodology, and reinforce the importance of systems measuring of utilization of pluvial water, taking into account important aspects to users security